1982
DOI: 10.2307/1540982
|View full text |Cite
|
Sign up to set email alerts
|

INHIBITORY EFFECT OF HISTAMINE ON THE RELEASE OF MELANIN-DISPERSING HORMONE IN THE FIDDLER CRAB,UCA PUGILATOR

Abstract: Histamine (HA), a stimulator of H, and H 2 receptors, produced dose-dependent inhibition of the melanin dispersion which normally occurs when fiddler crabs, Uca pugilator, are transferred from a white to a black background. The HA precursor L-histidine, and 4-methyl histamine (4-MeHA), an H 2 receptor agonist, also inhibited melanin dispersion. 2-Methyl histamine (2-MeHA), an H, receptor agonist, enhanced melanin dispersion. The inhibitory effects of HA and 4-MeHA were abolished by the H 2 receptor blocker met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1984
1984
2007
2007

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 44 publications
0
1
0
Order By: Relevance
“…In addition it has been demonstrated that HA mediates presynaptic inhibition in the escape reaction of the Procambarus clarkii crayfish (el Manira and Clarac, 1994), as well as presynaptic inhibition of primary olfactory afferents in lobster (Wachowiak and Cohen, 1999). It is known that HA injected into the circulation inhibits the black pigment dispersion that normally occurs in crabs transferred from a white to a black background in a dose-dependent manner (Hanumante and Fingerman, 1982). Recently we found that plasma levels of HA in the crayfish fluctuate during the day, reaching a maximum value at daybreak (Cebada et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…In addition it has been demonstrated that HA mediates presynaptic inhibition in the escape reaction of the Procambarus clarkii crayfish (el Manira and Clarac, 1994), as well as presynaptic inhibition of primary olfactory afferents in lobster (Wachowiak and Cohen, 1999). It is known that HA injected into the circulation inhibits the black pigment dispersion that normally occurs in crabs transferred from a white to a black background in a dose-dependent manner (Hanumante and Fingerman, 1982). Recently we found that plasma levels of HA in the crayfish fluctuate during the day, reaching a maximum value at daybreak (Cebada et al, 2006).…”
Section: Introductionmentioning
confidence: 99%